Trend Analysis of Pakistan Railways Based on Industry Life Cycle Theory - Li Xuemei; Khalid Mehmood Alam; Shitong Wang (Journal of Advanced Transportation)
The core purpose of this paper was to analyze the trend analysis of Pakistan railways from the year 1950 to 2015, using the principal component analysis method and industrial life cycle theory. Industrial life cycle theory, the development trend analysis of Pakistan railway industry, entails four stages: introduction, growth, maturity, and decline. The results indicated that railway industry in Pakistan was at its pinnacle in the middle of the seventies and thereafter the decline of railway industry was observed. The main reasons behind the decline were underinvestment, political interference, and the rise of the same-sector competitor, the National Logistics Cell (NLC). From the year 2011, it experienced an upward trend of combined utility curve and showed a new round of industry life cycle. To revive its previous glory, the current government has proposed a development document for Pakistan railways, Vision 2025. It is envisaged that railways share in transportation will be increased from current 4% to 20% by the year 2025, which seems to be an onerous challenge for the organization.